PENGARUH TEKNOLOGI KOMUNIKASI TERHADAP KEPUASAN PELANGGAN MELALUI STRATEGI PEMASARAN DIGITAL PADA CV SINAR ANUGRAH MACHNERY DI SIDOARJO - Muhammad Hakim A Maulana Ishaq; I Made Bagus Dwiarta; Ghozin; Faradilla Rosita; Suharyanto (Universitas Nusa Nipa Maumere, 2025)
This research aims to evaluate the impact of communication technology on customer satisfaction through the implementation of digital marketing strategies at CV Sinar Anugrah Machinery. Using a quantitative approach, data were collected from 112 customers using the proportionate stratified random sampling method to obtain a balanced representation. The analysis was conducted using the Partial Least Squares (PLS) approach with the SmartPLS software. The research results reveal that communication technology directly contributes positively to customer satisfaction and affects the effectiveness of digital marketing strategies. In addition, digital strategies have proven capable of increasing consumer satisfaction levels. This conclusion shows that the integration of communication technology in digital marketing can strengthen relationships with customers and increase loyalty. From a practical standpoint, companies are advised to continue leveraging the latest technology and strengthening their digital strategies to create superior customer experiences and maintain competitiveness in the ever-evolving market.